2021
DOI: 10.3390/ijerph18147350
|View full text |Cite
|
Sign up to set email alerts
|

A Cumulative Muscle Index and Its Parameters for Predicting Future Cognitive Decline: Longitudinal Outcomes of the ASPRA Cohort

Abstract: Sarcopenia and cognitive decline share the major risk factors of physical inactivity; previous studies have shown inconsistent associations. We aimed to identify the association of sarcopenia and its parameters with cognitive decline. The 3-year longitudinal outcomes of 1327 participants from the Aging Study of the Pyeongchang Rural Area (ASPRA) cohort were analyzed. Cognitive performance was evaluated using the Mini-Mental State Examination (MMSE), and sarcopenia was defined by the following: the original and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“… 31 ) Moreover, among various existing sarcopenic definitions, including the original and revised EWGSOP and the Asian Working Group for Sarcopenia (AWGS), only the SPS predicted future cognitive decline as assessed by the Mini-Mental State Examination (MMSE). 32 ) These results suggest that sarcopenia can be better captured by methods combining incremental sarcopenic burden in a manner similar to that used in the frailty index, rather than by an operational, dichotomous manner of determining sarcopenia.…”
Section: Findings and Implicationsmentioning
confidence: 88%
“… 31 ) Moreover, among various existing sarcopenic definitions, including the original and revised EWGSOP and the Asian Working Group for Sarcopenia (AWGS), only the SPS predicted future cognitive decline as assessed by the Mini-Mental State Examination (MMSE). 32 ) These results suggest that sarcopenia can be better captured by methods combining incremental sarcopenic burden in a manner similar to that used in the frailty index, rather than by an operational, dichotomous manner of determining sarcopenia.…”
Section: Findings and Implicationsmentioning
confidence: 88%
“…A combination of MCI and slow gait speed seems to be a strong predictor of further cognitive deterioration into AD, and is proposed as a subgroup of MCI named motoric cognitive risk syndrome [39]. Moreover, a newly derived sarcopenic index [37] showed that gait speed was the single most important indicator of cognitive decline in community-dwelling older adults [40]. We may speculate that for clinical practice, it could be important to identify motoric cognitive risk syndrome in order to possibly delay or decrease the risk of further cognitive decline with lifestyle interventions [41].…”
Section: Discussionmentioning
confidence: 99%